Chemotaxonomy in the Etlingera Genus from Sulawesi, Indonesia: Design and molecular docking of antioxidant marker - RINI HAMSIDI; KARMILAH KARMILAH; NUR SAADAH DAUD; MUHAMMAD HAJRUL MALAKA; AGUNG WIBAWA MAHATVA YODHA; MUSDALIPAH MUSDALIPAH; ARFAN ARFAN; SAHIDIN SAHIDIN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hamsidi R, Karmilah, Daud NS, Malaka MH, Yodha AWM, Musdalipah, Arfan, Sahidin. 2024. Chemotaxonomy in the Etlingera Genus from Sulawesi, Indonesia: Design and molecular docking of antioxidant marker. Biodiversitas 25: 449-457. Etlingera is one of the important genera in the Zingiberaceae family because of its potential uses. Several studies have been conducted on the Genus Etlingera as nutraceuticals and drugs. Recently new species have been found in the Sulawesi Region, Indonesia, namely E. canaria A.D.Poulsen and E. echinulate A.D.Poulsen. Based on literature review through sciencedirect and springer link, both species unknown for their chemical and pharmacological content, so it is necessary to continue to reveal the deeper potential. The fruits of E. calophrys (K.Schum.) A.D.Poulsen, E. canaria and E. echinulate were extracted with methanol by maceration method. The chemical content of each extract was analyzed using a Liquid Chromatography Mass Spectrometer (LCMS). Antioxidant activity was tested based on the 1,1-Diphenyl-2-Picrylhydrazyl (DPPH) method. The ability as an antioxidant is proven by the molecular interactions of marker compounds in inhibiting xanthine oxidase. The secondary metabolites contained in the fruit extracts of E. calophrys, E. canaria and E. echinulate are E-p-Coumatic acid, 1,5-Dimethyl citrate, Trimethyl citrate, Crocetin, Tanshinone IIA, Ethinyl Estradiol, Yakuchinone B, Anisalacetone, Yakuchinone A, Nobilin, ?-Estradiol, Momor-cerebroside I, Spinasterone, 12-Hydroxy-methyl abietate, Spinasterol, 2,3-Dihydroxypropyl oleate, 11-Octadecenoate acid methyl ester, Stigmastan-3,6-dione, b-Sitosterol- 3-O-b-D-glucopyranoside, Trilaurin, 28-O-Hexahydrophthalate and Fasciculol C. Yakuchinone A and Yakuchinone B are chemotaxonomic marker compounds identified in all species. The antioxidant properties of each extract of 42.27±0.53, 46.59±0.81 and 35.66±0.73 mg/L have been proven by the molecular interactions of the marker compounds in their ability to act as xanthine oxidase inhibitors. The compounds Yakuchinone A and Yakuchinone B are thought to be responsible for the pharmacological activity of the species E. calophrys, E. canaria and E. echinulate. Yakuchinone A and Yakuchinone B are marker compounds because they are distributed in all samples.